Summer Fertigation of Dairy Slurry Reduces Soil Nitrate Concentrations and Subsurface Drainage Nitrate Losses Compared to Fall Injection - Gamble, Joshua D.; Feyereisen, Gary W.; Papiernik, Sharon K.; Wente, Chris D.; Baker, John M. (Frontiers in Sustainable Food Systems, 2018)
Leaching of nitrate (NO3-N) from manure-applied cropping systems can represent a substantial N-loss to the environment for dairy farms, particularly in fields with artificial subsurface drainage. In this on-farm study, we used a Before/After analysis to assess the effectiveness of summer fertigation with reduced manure rates (years 2010-2015) vs. fall injection (2007-2009) of dairy slurry in terms of subsequent corn silage yield, corn N removal, soil NO3-N distribution, and NO3-N losses in subsurface tile drainage from a 65-ha field in Minnesota, USA. Yield was similar between periods (average of 18.8 Mg ha−1), but crop %N, N removal, and manurial N-use efficiency (MNUE) were 15, 12, and 126% greater during the fertigation than injection period. Fertigation reduced spring soil NO3-N concentrations to 60-cm depth by an average of 53% relative to injection, except in the 15–30 cm increment, where no difference was found. Similarly, fall soil NO3-N concentrations from 30 to 90 cm were 48% lower, on average, under fertigation than injection. Weekly flow-weighted mean NO3-N concentration in tile drainage was lower during fertigation (47.7 mg L−1) than injection (56.8 mg L−1), although mean weekly drainage depth was greater during fertigation (2.3 vs. 1.1 mm). This resulted in similar weekly loads between periods (mean of 0.96 kg NO3-N ha−1). For non-snowmelt flow, relationships between drainage and NO3-N load showed log–log slopes of near 1.0 for injection and 0.97 for fertigation, indicating dilution of concentrations with increased flow during fertigation, but not during injection. Differing intercepts indicated a treatment effect of fertigation independent of flow effects, and corresponded to loads of 5.9 kg NO3-N ha−1 for injection and 4.7 kg NO3-N ha−1 for fertigation, a reduction of 20% at a 10 mm weekly flow depth. The magnitude of the reduction in load increased to 22% at a 25 mm weekly flow depth. Results suggest that summer fertigation with attendant reduction in application rate is a viable method for reducing drainage NO3-N losses without impacting yield of irrigated silage corn in the U.S. Midwest.